Kredibilitas dan Kekuatan Selebgram dalam Meningkatkan Minat Beli pada Toko Online di Instagram - Muhamad Alvi Irpansyah; Asep M Ramdan; R. Deni Muhammad Danial (COSTING : Journal of Economic, Business and Accounting, 2019)
One of the strategy that can be use in increasing consumer buying interest is by increasing the attractiveness of advertisements on Instagram, one of them is the endorsement strategy. The study aims to determine about the selebgram credibility and power to increase purchase intention on online store in instagram, as well as to see how much the influence of credibility and power of selebgram to purchase intention partially or simultaneously. The method use in this research is descriptive verificative and quantitative approaches with multiple linear regression as a data analysis technique. Research result obtained show that credibility, power and purchase intentions of online store on instagram in the good category. The magnitude of the effect of credibility and power on purchases intention on instagram by Rachel Vennya after testing simultaneously and partially have a positif and significant influence. It’s amounted to 51,2%, while the remaining 48,8% are influenced by other variables not examined in this research. Keywords: Credibility, Power, Selebgram, Celebrity Endorsement, Purchase Intention